SPIRITUAL MASTER IN THE PATH OF KNOWLEDGE IN INDIAN TRADITION - McMichael, James D (Journal of Dharma, 2020)
While there have been slow but continuous changes in the practices and beliefs of Hinduism as a religion, the essential spiritual teachings of Hinduism have remained largely unaltered. The spiritual teachings however, concerning the path of knowledge (jñãna-mãrga) survive as the most distinctive features of this spirituality.